2014
DOI: 10.14814/phy2.12240
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin inhibits renin release from juxtaglomerular cells via endothelin receptors A and B via a transient receptor potential canonical-mediated pathway

Abstract: Renin is the rate‐limiting step in the production of angiotensin II: a critical element in the regulation of blood pressure and in the pathogenesis of hypertension. Renin release from the juxtaglomerular (JG) cell is stimulated by the second messenger cAMP and inhibited by increases in calcium (Ca). Endothelins (ETs) inhibit renin release in a Ca‐dependent manner. JG cells contain multiple isoforms of canonical transient receptor potential (TRPC) Ca‐permeable channels. The proposed hypothesis is that endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Therefore the amount of renin is a limiting step during the production of Ang II, the main RAS component that acts as a critical element to the regulation of blood pressure and CKD pathogenesis. Renin release by JG cells is stimulated by cAMP and is inhibited by an increase in intracellular calcium levels (Ortiz-Capisano et al 2013) and endothelins in a calcium dependent way (Ortiz-Capisano et al 2014). cAMP is a second messenger used for the transduction of intracellular signals in diverse biological processes, having an important role in stimulating renin gene expression.…”
Section: Involvement Of Adenosine In Renal Vascular Tone Regulationmentioning
confidence: 99%
“…Therefore the amount of renin is a limiting step during the production of Ang II, the main RAS component that acts as a critical element to the regulation of blood pressure and CKD pathogenesis. Renin release by JG cells is stimulated by cAMP and is inhibited by an increase in intracellular calcium levels (Ortiz-Capisano et al 2013) and endothelins in a calcium dependent way (Ortiz-Capisano et al 2014). cAMP is a second messenger used for the transduction of intracellular signals in diverse biological processes, having an important role in stimulating renin gene expression.…”
Section: Involvement Of Adenosine In Renal Vascular Tone Regulationmentioning
confidence: 99%
“…Importantly, multiple regression analysis revealed that ET-1 is not only an independent determinant of both the blood pressure rise and proteinuria in PE, but also a renin suppressor [Verdonk et al 2015]. Animal studies support the latter [Ritthaler et al 1995; Ortiz-Capisano, 2014].…”
Section: Endothelin-1 In Clinical Pre-eclampsiamentioning
confidence: 99%
“…16,17 Moreover, ET-1 has been reported to suppress renin release in animal models. 18,19 The cause of the RAAS suppression in preeclampsia has always been elusive. Given the reduced circulating volume in preeclampsia, the opposite should have occurred.…”
mentioning
confidence: 99%